Being a mother, detesting the rose: a transgressive vision of femininity in Blanca Varela’s Valses y otras falsas confesiones (1972) - Bermejo Lozano, Adriana (2023)
This article proposes to study the link between the representation of motherhood and the demystification of the rose as constitutive processes of the transgressive vision of femininity in Blanca Varela’s collection of poems Valses y otras falsas confesiones (1972). To this end, the autobiographical experience of motherhood as an event that transforms Varela’s conception, language and poetic voice from this collection of poems onwards is taken as a starting point. From this experiential framework, we analyse the poems in which the theme of motherhood and childhood is addressed, as well as those in which the rose appears, as paradigmatic examples of the evolution of a demystifying poetics that violates the classical poetic conventions surrounding the feminine. By way of conclusion, the connection between the maternal and floral symbols as motifs used by the poetic voice to transgress and broaden poetic representations of women is ratified.